ANALISIS PENGARUH CORPORATE GOVERNANCE STRUCTURE TERHADAP FEE AUDIT EKSTERNAL - Meliani Mukti; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2016)
The aim of this study is to examine the influence of corporate governance structure such as non- executive board independence, non-executive board size. non-executive hoard meeting, audit committee size, audit committee meeting, audit committee expertise.and ownership concentration to the external audit fee. 17w population used in this study consist of manufacture firms listed on the Indenesia Stock Exchange in 2012-2014. The sampling method used in this study is purposive sampling and obtained 33 samples. This study uses multiple regression analysis for hypotheses testing. The results of this study show that variables of non-executive board size and audit committee size had positively significant influence on external audit fee, while variables of non- executive board independence, non-executive board meeting, audit committee meeting, audit committee expertise. and ownership concentration had no significant influence on external audit fee.